EFFECTIVENESS OF USING ANIMATION MEDIA ON UNDERSTANDING MEANING THROUGH THE IMPLEMENTATION OF CONTEXTUAL LEARNING - Febriani, Suci Ramadhanti; Wicaksono, Meidias Abror; Mela, Desriliwa Ade; Nursyahida, Nursyahida (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2024)
The high intensity of use of technological media is increasing rapidly. This encourages teachers to use animation media for learning Arabic in understanding meaning through a contextual learning system. On that basis, this research aims to test the effectiveness of using animation media on understanding meaning through the implementation of contextual learning. This research uses a mix method design with a quantitative approach to test the effectiveness of learning Arabic using animation media, while the qualitative approach serves to analyze the meaning produced by students from animation media based on contextual learning. The data used were the scores of 36 Arabic language and literature study program students at UIN Imam Bonjol Padang, while the analysis technique used was a t-test with SPSS 16.00 and Milles and Hubberman theory for qualitative data analysis. The results of the research show that the use of animation media to understand meaning through the implementation of contextual learning is effective in increasing students' grades, while in the process of understanding denotative and connotative meaning there are 15 sentences. Research findings show that the use of animation media can provide students with the opportunity to analyze meaning contextually and creatively in determining the object of study. This research is limited to the use of samples, so the researcher recommends further research to use a research design with more varied objects and samples.